Make them dry, keep them dry: Traditional and modern techniques and practices to store and conserve seeds safely - Vernooy, Ronnie; Adokorach, Joyce; Aluso, Lilian; Gupta, Arnab; John, Robert; Mohamed, Mubiru Daudi; Mushiga, Joy; Muhumuza, Jasper; Nyabasha, Sylvia; Otieno, Gloria Atieno (2022)
This brief presents the highlights of a training workshop on traditional and modern techniques and practices to store and conserve seeds safely. The workshop was held at the NARO-Bulindi research station in Hoima, Uganda, in August 2022. Participants were members of community seed banks of Kenya and Uganda, and staff of research and development organizations engaged in resilient seed systems and community seed banking from Kenya, Uganda, Zambia and Zimbabwe. Topics addressed included the principles of quality seed production and adequate seed storage, and the use of traditional containers, botanical products, airtight containers, desiccants such as silica gel and zeolite beads, and hygrometers.